Situational Analysis Improving Economic Outcomes by Expanding Nutrition Programming in Tajikistan - World Bank; UNICEF (World Bank, Washington, DC, 2013)
Undernutrition in Tajikistan remains an important public health challenge, albeit a hidden problem. Stunting, iodine deficiency, and maternal and child anemia represent the largest burden of undernutrition in Tajikistan. In 2009, around 29 percent of children in all regions of the country were stunted. Iodine deficiency was observed in 53 percent of children and in 58.6 percent of women. The national prevalence of anemia in children was 28.8 percent; however, rates were as high as 39.8 percent in Ghorno-Badakhshan Autonomous Province and in 32 percent directly ruled districts (DRD). The prevalence of anemia among mothers was 24.2 percent. The long-term effects of these conditions negatively affect the health of adults throughout their life, as well as their potential productivity in the work force and possible economic contribution to the nation. The highest priority interventions will improve infant and young child feeding. Strengthening and scaling up breastfeeding promotion will save lives and help to reduce stunting as would complementary feeding for babies six months and older. Promoting exclusive breastfeeding for infants under six months is the most efficacious intervention to save lives, averting nearly 20 percent of deaths in children under-five. Effective programs need to be designed to make more women aware of the benefits of breastfeeding and sound nutrition. A comprehensive, multi-sector approach is needed to ensure success of these interventions. This report also makes several other recommendations including: supplementing pregnant women with either iron folic acid or multiple micronutrients, maintain twice-annually vitamin A supplementation, implementing a deworming program, support for flour fortification, scale up and maintain zinc for the management of diarrhea, and address the underlying and basic causes of undernutrition through other sectors.